Peran dan Upaya Guru dalam Mengatasi Kesulitan Belajar Membaca Siswa SD Kelas Rendah - Jihan Fitri Syahrani; Danang Dwi Basuki (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The difficulty of learning to read is one of the problems in the learning of low-grade elementary school students. Difficulty in learning to read is a problem that teachers and parents should not take lightly. The role of the teacher is very important in overcoming this. The method used in this research is the descriptive qualitative method. Data collection was carried out through structured interviews to explore the data needed in the research. Based on the results of the study, it was shown that there were several factors that influenced students to experience difficulties in learning to read, including family factors, internal factors, cellphone factors, and environmental factors. In addition, students who have difficulty learning to read can have a negative impact on their academics. Efforts made by teachers vary, ranging from using interesting methods such as literacy methods, reading corners, and conducting additional classes to learn to read.